5x+9=2x+13

Simple and best practice solution for 5x+9=2x+13 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5x+9=2x+13 equation:


Simplifying
5x + 9 = 2x + 13

Reorder the terms:
9 + 5x = 2x + 13

Reorder the terms:
9 + 5x = 13 + 2x

Solving
9 + 5x = 13 + 2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-2x' to each side of the equation.
9 + 5x + -2x = 13 + 2x + -2x

Combine like terms: 5x + -2x = 3x
9 + 3x = 13 + 2x + -2x

Combine like terms: 2x + -2x = 0
9 + 3x = 13 + 0
9 + 3x = 13

Add '-9' to each side of the equation.
9 + -9 + 3x = 13 + -9

Combine like terms: 9 + -9 = 0
0 + 3x = 13 + -9
3x = 13 + -9

Combine like terms: 13 + -9 = 4
3x = 4

Divide each side by '3'.
x = 1.333333333

Simplifying
x = 1.333333333

See similar equations:

| 4-(3x+2)=7(2x+5) | | -4+3x=-6+10 | | -15u-6u-12u-20=13 | | 4x^2+4xy+y^2-100= | | 14.50=p-53 | | X=3y-2400 | | -55-11x=7(9-10x) | | 3x+7y-21=0 | | -(b-3)+7=4 | | 6x+4[7-(x-2)]= | | 2n^2-2n+5=400 | | 5x+1+12x-1=17 | | 5(x-14)=4(x-7) | | 4y+1=56-9 | | 7x-2+3= | | 12=7+3x+1 | | 10-p=-8 | | x^2+10x=-38 | | -3(2x+1)+(3x+2)= | | 1.2+1.5x=5.7 | | 2(d-6)-1=1 | | -2(s-4)-2=2 | | (x+3)(x-2)(x-8)=0 | | n^2+n=22 | | 2y^2-14y+24=0 | | .3x-4x-1=3 | | x+14+x+8=10 | | ex-2=12 | | 2(k-5)-7=1 | | g(p+3)=2x^2+2x+3 | | (4x-3)*(3x-2)= | | 14h-7h=-14 |

Equations solver categories